Discovery Learning Based E-Worksheet Assisted with Google Docs to Grow Higher Order Thinking Skills of Junior High School Students - F. N. Muhammad; D. Rosana; P. W. Hastuti (Universitas Negeri Yogyakarta, 2022)
This study aimed to 1) find out the feasibility of the E-worksheet based on discovery learning with Google Docs product, 2) explain the practicality of the E-worksheet based on discovery learning with Google Docs product, and 3) understand the effectiveness of the E-worksheet based on discovery learning with Google Docs product to grow higher order thinking skills (HOTS) of VIII grade junior high school students on the simple machine topic. The study was a research and development (R and D) with the 4D model. The subjects were 32 students of VIIIA class in SMPN 4 Pakem. The instruments were product validation sheet, students’ response questionnaire, pre-test and post-test questions, and learning observation sheet. The feasibility and practicality of the product were analyzed using score conversion. The results of the pre-test and post-test were analyzed using qualitative and quantitative descriptive analysis to find out the effectiveness of the product. The research concluded that 1) the E-worksheet based on discovery learning with Google Docs product was very feasible, both in the material and media aspects, 2) the E-worksheet based on discovery learning with Google Docs was practical based on the teacher and students’ responses, and 3) the E-worksheet based on discovery learning with Google Docs was effective to build the HOTS of the students.